Understanding the enigma of a novel pediatric disease, multisystem inflammatory syndrome in children: when COVID-19 throws a curveball at children's health - Maqsood, Maryam (International Journal of Advances in Medicine, 2023)
Multisystem inflammatory syndrome in children (MIS-C) is a rare and potentially life-threatening condition that has emerged as a post-infectious complication of COVID-19. MIS-C is characterized by widespread inflammation affecting multiple organ systems, including the heart, lungs, kidneys, and gastrointestinal tract. The condition primarily affects school-aged children and adolescents, with most cases occurring several weeks after a COVID-19 infection. The exact pathophysiology of MIS-C is not yet fully understood, but it is thought to result from an abnormal immune response triggered by the SARS-CoV-2 virus. The clinical presentation of MIS-C is highly variable, and patients may present with fever, rash, conjunctivitis, abdominal pain, vomiting, diarrhea, and cardiac dysfunction. Early recognition and diagnosis of MIS-C are crucial for the prompt initiation of treatment, which typically involves immunomodulatory therapy and supportive care. The diagnosis of MIS-C is based on a combination of clinical and laboratory findings, including elevated inflammatory markers, cardiac biomarkers, and evidence of recent SARS-CoV-2 infection. The management of MIS-C is challenging, and treatment strategies continue to evolve as our understanding of the condition improves. Ongoing research is focused on optimizing diagnostic and therapeutic approaches to improve outcomes for affected children. This review article provides an overview of the current state of knowledge regarding MIS-C, including its epidemiology, clinical presentation, diagnostic evaluation, and management strategies.